ApoE suppresses atherosclerosis by reducing lipid accumulation in circulating monocytes and the expression of inflammatory molecules on monocytes and vascular endothelium - Gaudreault, Nathalie (2011)
OBJECTIVE: We investigated atheroprotective properties of apoE beyond its ability to lower plasma cholesterol. We hypothesized that apoE reduces atherosclerosis by decreasing lipid accumulation in circulating monocytes and the inflammatory state of monocytes and the vascular endothelium. METHODS AND RESULTS: We developed mice with spontaneous hyperlipidemia with and without plasma apoE: Hypomorphic apoE mice deficient in low-density lipoprotein receptor (Apoe(h/h)Ldlr(–/–)) were compared to Apoe(–/–)Ldlr(–/–) mice. Despite 4-fold more plasma apoE than WT mice, Apoe(h/h)Ldlr(–/–) mice displayed similar plasma cholesterol as Apoe(–/–)Ldlr(–/–) mice but developed 4-fold less atherosclerotic lesions by 5 months of age. The aortic arch of Apoe(h/h)Ldlr(–/–) mice showed decreased endothelial expression of ICAM-1, PECAM-1, and JAM-A. In addition, Apoe(h/h)Ldlr(–/–) mice had less circulating leukocytes and pro-inflammatory Ly6C(high) monocytes. These monocytes had decreased neutral lipid content and reduced surface expression of ICAM-1, VLA-4, and L-Selectin. Apoe(h/h)Ldlr(–/–) mice displayed increased levels of apoA1-rich HDL that were potent in promoting cellular cholesterol efflux. CONCLUSIONS: Our findings suggest that apoE reduces atherosclerosis in the setting of hyperlipidemia by increasing plasma apoA1-HDL that likely contribute to reduce intracellular lipid accumulation and thereby the activation of circulating leukocytes and the vascular endothelium.